Dissociation of the respiratory syncytial virus F protein-specific human IgG, IgA and IgM response - Borochova, Kristina; Niespodziana, Katarzyna; Focke-Tejkl, Margarete; Hofer, Gerhard; Keller, Walter; Valenta, Rudolf (Scientific reports, 2021)
Human respiratory syncytial virus (RSV) is one of the most important causes of severe respiratory tract infections in early childhood. The only prophylactic protection is the neutralizing antibody, palivizumab, which targets a conformational epitope of the RSV fusion (F) protein. The F protein is generated as a F0 precursor containing two furin cleavage sites allowing excision of the P27 fragment and then gives rise to a fusion-competent version consisting of the N-terminal F2 subunit and the a C-terminal F1 subunits linked by two disulphide bonds. To investigate natural human F-specific antibody responses, F2 conferring the species-specificity of RSV, was expressed in Escherichia coli . Furthermore, the F0 protein, comprising both subunits F2 and F1, was expressed as palivizumab-reactive glycoprotein in baculovirus-infected insect cells. Six overlapping F2-derived peptides lacking secondary structure were synthesized. The analysis of IgG, IgA and IgM responses of adult subjects to native versions and denatured forms of F2 and F0 and to unfolded F2-derived peptides revealed that mainly non-conformational F epitopes, some of which represented cryptic epitopes which are not exposed on the proteins were recognized. Furthermore, we found a dissociation of IgG, IgA and IgM antibody responses to F epitopes with F2 being a major target for the F-specific IgM response. The scattered and dissociated immune response to F may explain why the natural RSV-specific antibody response is only partially protective underlining the need for vaccines focusing human antibody responses towards neutralizing RSV epitopes.